An econometric analysis of the determinants of growth in the Kingdom of Tonga, 1970-1998 : a research thesis submitted in partial requirement for the degree of Master of Applied and International Economics at Massey University - Faletau, Siosaia Tupou (Massey University, 1999)
The importance of determining the factors that contribute to economic growth is vital in the case of Tonga because of the benefits and advantages it provides for the people and their future development. The main objective of this study is to analyse and investigate empirically the macroeconomic factors that promote economic growth and development in Tonga. Economic theories and various studies have presented the variables that may affect growth. These include investment (domestic and foreign), labour force, exports and imports, fiscal policies, tourism receipts, private remittances, foreign aid and its various components. Foreign resources such as aid and private remittances play an important role in the development of small island economies and Tonga's heavy reliance on these factors may also explain their contribution to growth. The study uses a neoclassical production function to examine the relationships between economic growth in Tonga and the proposed determinants listed above. The cointegration method of Auto-Regressive Distributed Lag is utilised in the analysis. The empirical evidence indicates that factors making a positive contribution to economic growth in Tonga are the growth in exports, tourism receipts, openness to trade, government consumption expenditure, bilateral aid, grant aid and imports. The loan aid, multilateral aid, technical co-operation grants and private remittances, while significant in most cases, show a decline over time. Natural disasters and external market shocks have a strong adverse effect on Tonga's growth rate. The issue of macroeconomic management is stressed in this study as the key role to be played by the government in order for the available resources to be allocated to the productive sectors of the economy. This can be undertaken through setting stable macroeconomic environment, introducing and maintaining growth-oriented policies and structural reforms in some of the key sectors of the economy. Research should be concentrated on high value niche products and promoting technological development to support the diversification in the export and tourism sectors. Measures should also be adopted to monitor the effectiveness of utilising foreign aid projects, as current aid flows show a decline.
Keywords: Tonga; Economic development; Econometric models; Economic conditions